Henrik S. Nissen (ed.), Scandinavia during the Second World War, Oslo: Universitetsforlaget; Minneapolis: The University of Minnesota Press, 1983, 407 s., 183,00 kr. - Petersen, Nikolaj (Politica, 1984)
-